2018
DOI: 10.1002/ange.201808320
|View full text |Cite
|
Sign up to set email alerts
|

trans‐Cyclooctenes as Halolactonization Catalysts

Abstract: The strained olefins in trans-cyclooctenes serve as efficient catalysts for halolactonizations,i ncluding bromolactonizations and iodolactonizations.T he trans-cyclooctene framework is essential for excellent catalytic performance, and the substituents also play important roles in determining efficiency.These results are the first demonstration of catalysis by atrans-cyclooctene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We then investigated the catalytic activity of 10a toward the bromolactonization of the alkenoic acid 15 (Table 3 ). In our previous work, we developed monosubstituted TCOs as catalysts for bromolactonization (Table 3 , entries 2 and 3) 8a and found that the substituents on the TCOs have significant effects on the catalytic activity; we identified 17 bearing a benzyl group as the most active catalyst. The investigation of the catalytic efficiency of 10a bearing two benzyl groups revealed that 10a was superior to 17 (Table 3 , entry 1).…”
Section: Table 1 Optimization Of the Cross-coupling Of ...mentioning
confidence: 99%
“…We then investigated the catalytic activity of 10a toward the bromolactonization of the alkenoic acid 15 (Table 3 ). In our previous work, we developed monosubstituted TCOs as catalysts for bromolactonization (Table 3 , entries 2 and 3) 8a and found that the substituents on the TCOs have significant effects on the catalytic activity; we identified 17 bearing a benzyl group as the most active catalyst. The investigation of the catalytic efficiency of 10a bearing two benzyl groups revealed that 10a was superior to 17 (Table 3 , entry 1).…”
Section: Table 1 Optimization Of the Cross-coupling Of ...mentioning
confidence: 99%
“…[4b,4c] However, to the best of our knowledge, the behavior of trans-cyclooctene derivatives as chiral ligands for asymmetric catalysis is unknown despite their potential as novel molecular-catalyst platforms. [6] Here, we introduce transcyclooctenes as asymmetric ligands for the rhodium-catalyzed 1,4-additions of organotin reagents and describe their performance, thereby providing new chiral platforms for asymmetric catalysis.…”
mentioning
confidence: 99%